Perbuatan Melawan Hukum atas Proses Penarikan Secara Paksa Objek Jaminan Fidusia: Studi Putusan Nomor 650/PDT.G/2023/PN.Mdn, Nomor 172/Pdt.G/2020/PN.Amb, Nomor 198/Pdt.G/2020/PN JKT.Sel - Sonta Lumbantobing; Tan Kamello; Rosnidar Sembiring (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The analysis of unlawful acts in the process of forcible repossession of fiduciary collateral in Indonesia is based on Law Number 42 of 1999 and Constitutional Court Decision Number 18/PUU-XVII/2019. The approach used is normative juridical by examining Court Decisions Number 650/PDT.G/2023/PN.Mdn, 172/Pdt.G/2020/PN.Amb and 198/Pdt.G/2020/PN.Jkt.Sel to assess the balance between creditor rights and debtor protection. The results indicate that repossession conducted without proper procedure constitutes an unlawful act that violates legal certainty and grants the debtor the right to claim restitution or compensation. The courts emphasize the importance of proving default, due process and the prohibition of unilateral actions.